Tumor burden score dictates prognosis of patients with combined hepatocellular cholangiocarcinoma undergoing hepatectomy - Deng, Gang; Ren, Jun-kai; Wang, Hai-tao; Deng, Liang; Chen, Zu-bing; Fan, You-wen; Tang, Ya-jun; Zhang, Tong; Tang, Di (Frontiers in Oncology, 2023)
Background: The prognostic value of the tumor burden score (TBS) in patients with combined hepatocellular-cholangiocarcinoma (cHCC-CCA) remains unknown. This study aimed to investigate the impact of TBS on long-term outcomes after surgery. Methods: Patients who underwent radical-intent resection between 2013 Jun and 2019 Dec were retrospectively reviewed. Kaplan-Meier curves were used to analyze patient survival, and disease-free survival (DFS) and overall survival (OS) were examined in relation to TBS. Results: A total of 178 patients were included in this study, with 119 in the training cohort and 59 in the validation cohort. Kaplan-Meier curves showed that TBS was a strong prognostic indicator in cHCC-CCA patients. Elevated TBS was associated with poorer DFS and OS (both P-value < 0.001) and was identified as an independent prognostic indicator. In addition, the prognostic value of TBS outperformed tumor size and number alone, microvascular invasion (MVI) and lymph node invasion. The prognostic significance of TBS was confirmed by the internal validation cohort. Conclusions: The present study suggested the significance of tumor morphology in assessing the prognosis of cHCC-CCA patients who undergoing curative resection. The TBS is a promising prognostic index in cHCC-CCA patients. Elevated TBS was related to a lower long-term survival rate and was identified as an independent risk factor for poor DFS and OS. Further research is needed to verify our results.